Effect of the Task Hierarchy Analysis Model of Instruction on the Biology Students’ Performance and Attitudes in Osun State - OMOTAYO, K. A.; OSUALA, Ogechi Rita (Ilorin Journal of Education, 2023)
The study examined the impact of the task hierarchy analysis model of instruction on the Biology students’ performance and attitudes. The study employed a quasi-experimental pre-test and post-test control group design. Using a multistage sampling technique, the sample consists of 379 senior high school two Biology students from 12 public secondary schools in three Local Government Areas (LGAs) in Osun State.There were experimental and control groups in the sample. Two research instruments, the Biology Performance Test (BPT) and the Biology Attitude Scale (BAS), with respective reliability values of 0.83 and 0.76, were employed to collect pertinent data for the study. The research questions posed were answered with descriptive statistics, and the results were illustrated with bar charts and at a significance level of 0.05 while the hypotheses were tested using appropriate inferential statistics such as the t-test and Analysis of Covariance (ANCOVA).The results of the study indicated that there is a statistically significant difference between the mean achievement scores of students exposed to the task hierarchy analysis model of instruction and their counterparts in the control group. The results of the study demonstrated that students taught the notion of biology using the task hierarchy analysis style of instruction have a significantly different attitude than their counterparts in the control group. The task hierarchy analysis approach of education was advocated, among others, for use in the secondary school Biology classroom.